Carta de Antonio R. Barceló a Roberto H. Todd - Barceló, Antonio R.; Todd, Roberto H. (My University, 1931)
Invitación a la Asamblea Magna del Partido Unión.
Keywords: Partido Unión de Puerto Rico; Barceló, Antonio R., 1868-1938; Unión de Puerto Rico